Stress distribution on the L1/L2 endplates under multiaxial loads: A finite element study - Hasyid Ahmad Wicaksono; Muhammad Rafli; Muhamad Bilal; M. Danny Pratama Lamura; Mohamad Izzur Maula; Athanasius Priharyoto Bayuseno; Tri Indah Winarni; Jamari Jamari (Universitas Muhammadiyah Magelang, 2025)
Understanding stress distribution on lumbar vertebral endplates is essential for predicting mechanical failure and guiding clinical interventions. Therefore, this study aims to investigate the von Mises stress patterns on the L1/L2 endplates under multiaxial loading using a 3-dimensional finite element (FE) model derived from CT imaging of a healthy 55-year-old male. Anatomical structures were reconstructed in Mimics 21.0, and simulations were conducted in ANSYS Workbench 2023 R2. Material properties for cortical bone, cancellous bone, and intervertebral disc were assigned based on validated biomechanical data. A compressive load of 500 N and multiaxial moments ranging from 2.5 to 10 N•m were applied to simulate physiological movements, while the inferior surface of L2 was fully constrained to reflect realistic boundary conditions. The results showed that the superior endplate experienced the highest von Mises stress, particularly during flexion and lateral bending, indicating increased vulnerability to mechanical overload. Extension loading significantly reduced stress on both endplates, with a 60.54% decrease on the superior endplate and 69.17% on the inferior endplate. Stress distribution was asymmetrical and was influenced by anatomical features, such as cortical thickness and trabecular alignment. These results show the superior endplate as a biomechanically critical region prone to degeneration, emphasizing its importance in implant design, preventive strategies, and risk assessment for microfracture in high-risk populations.